ANALISIS BIMBINGAN PENGEMBANGAN WAWASAN KARIR DI KELAS V SD NEGERI 27 MEBUNG. DESA MEBUNG KECAMATAN ALOR TENGAH UTARA KABUPATEN ALOR - Drasmi Inra Kamata; Elsanoza Puling, Jellian Eriance Padalani, Yessy Mata, Petrus Mau Tellu Dony, Antonius A. Saetban, N (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This study aims to analyze the implementation of career awareness guidance in Grade V at SD Negeri 27 Mebung, Alor Tengah Utara District, Alor Regency. The research uses a descriptive qualitative approach with data collection techniques including observation and interviews. The findings show that the implementation of career guidance services is integrated into thematic learning through activities such as storytelling about professions, workplace visits, and role-play. Teachers play an active role as facilitators who help students recognize their interests and potential, although there are still limitations in teachers’ understanding of career counseling approaches for young children. Evaluation is carried out through observation, interviews, and the use of interest exploration instruments, accompanied by appreciation for the talents and interests displayed by students. Therefore, the integration of career guidance into the basic curriculum needs to be strengthened through teacher training and collaboration among schools, parents, and the community.